Modelagem física de plataformas de transferência de carga reforçadas com geossintéticos utilizando um sistema estratificado de solos transparentes - Santos, Dhionata Wyllian Moreira (2023)
Trapdoor tests have been commonly used in laboratory environments to simulate the behavior of piled embankments. Although this set can be simply represented by a system of trapdoors, the complexity imposed by the interaction between the granular layer, soft soil and the piles demands further investigations. In addition, limited studies have been carried out to investigate the deformation patterns and internal mechanisms of load transfer platforms reinforced with geosynthetics. This type of investigation is intrinsically complex in view of the interaction between the different components. Therefore, complete understanding depends on both qualitative and quantitative analyses, considering the performance of all components. This study proposes the use of a layered transparent system to evaluate the behavior of load transfer platforms reinforced with geosynthetic through experimentation by physical models. This approach involved the use of two families of transparent soils: fused quartz and Laponite RD. The layered models of transparent soils proved to consistently simulate the behavior of piled embankments. The Digital Image Correlation (DIC) technique was used to monitor the displacement field of the layered systems. The physical models’ responses produced deformations that followed the triangular expanding pattern. Furthermore, the deflection pattern of load transfer platforms was found to behave similarly to continuous concrete beams subjected to bending. The presence of geosynthetic reinforcement reduced, in general, the displacements and deformations of the models. From the point of view of load transfer, the use of geosynthetics reduces the effect of soil arching only when they are located within the tensile zone of the granular layer.